2017
DOI: 10.15446/agron.colomb.v35n2.63974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deficit irrigation on the postharvest of pear variety Triunfo de Viena (Pyrus communis L.) in Sesquile (Cundinamarca, Colombia)

Abstract: A technique settled to optimize the use of water resources is known as Controlled Deficient Irrigation (CDI), for which this experiment was carried out to determine the effect of a three water laminae: 100 (T1), 25 (T2) and 0% (T3) crop's evapotranspiration (ETc) on the rapid growth phase of the pear fruit variety Triunfo de Viena.The fruit quality (fresh weight variation, osmotic potential, color, acidity, soluble solids, CO2 emission, dry matter, volume, firmness, ripeness index and moisture content) was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
2
Order By: Relevance
“…However, the difference between the two treatments in controlled atmospheres was not significant. These results were greater than those reported by Trujillo et al (2016) The storage time affected the value of b* in the onions analyzed. In the CT bulbs, the value of b* increased through the months of conservation.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…However, the difference between the two treatments in controlled atmospheres was not significant. These results were greater than those reported by Trujillo et al (2016) The storage time affected the value of b* in the onions analyzed. In the CT bulbs, the value of b* increased through the months of conservation.…”
Section: Resultscontrasting
confidence: 72%
“…Similar results were obtained by Cardoso et al (2016) in ''Bola Precoce'' onions, who reported that this parameter is affected by curing, obtaining a higher value (a* = -2.32) for onions that were cured in the field than for those that were cured with artificial hot air (a* = -2.05) and with artificially heated and dried air (a* = -1.76). In another study, Trujillo et al (2016) reported higher values than those obtained in the present work in ''Roja Ocañera'' (a* = 20.24), ''Peruana Inca Alto del Pozo'' (a* = 21.85), ''Peruana Inca Abrego'' (a* = 22.50) and ''Peruana Inca La Playa'' (a* = 21.75) onions. Different lowercase letters in the same row indicate a significant statistical difference (p \ 0.05) between treatments within each month.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation